Virologic efficacy of tenofovir, lamivudine and dolutegravir as second-line antiretroviral therapy in adults failing a tenofovir-based first-line regimen - Keene, CM; Griesel, R; Zhao, Y; Gcwabe, Z; Sayed, K; Hill, A; Cassidy, T; Ngwenya, O; Jackson, A; van Zyl, G; Schutz, C; Goliath, R; et al. (Lippincott, Williams and Wilkins, 2021)
Objective: Recycling tenofovir and lamivudine/emtricitabine (XTC) with dolutegravir would provide a more tolerable, affordable, and scalable second-line regimen than dolutegravir with an optimized nucleoside reverse transcriptase inhibitor (NRTI) backbone. We evaluated efficacy of tenofovir/lamivudine/dolutegravir (TLD) in patients failing first-line tenofovir/XTC/efavirenz or nevirapine. Design: Single arm, prospective, interventional study. Setting: Two primary care clinics in Khayelitsha, South Africa. Participants: Sixty adult patients with two viral loads greater than 1000 copies/ml. Intervention: Participants were switched to TLD with additional dolutegravir (50 mg) for 2 weeks to overcome efavirenz induction. Primary outcome: Proportion achieving viral load less than 50 copies/ml at week 24 using the FDA snapshot algorithm. Results: Baseline median CD4+ cell count was 248 cells/μl, viral load 10 580 copies/ml and 48 of 54 (89%) had resistance (Stanford score ≥15) to one or both of tenofovir and XTC. No participants were lost to follow-up. At week 24, 51 of 60 [85%, 95% confidence interval (CI) 73–93%] were virologically suppressed, six had viral load 50–100 copies/ml, one had viral load 100–1000 copies/ml, one no viral load in window, and one switched because of tenofovir-related adverse event. No integrase mutations were detected in the one participant meeting criteria for resistance testing. Virological suppression was achieved by 29 of 35 (83%, 95% CI 66–93%) with resistance to tenofovir and XTC, 11 of 13 (85%, 95% CI 55–98%) with resistance to XTC, and six of six (100%, 95% CI 54–100%) with resistance to neither. Conclusion: A high proportion of adults switching to second-line TLD achieved virologic suppression despite substantial baseline NRTI resistance and most not suppressed had low-level viraemia (≤100 copies/ml). This suggests recycling tenofovir and XTC with dolutegravir could provide an effective second-line option.